Tumor necrosis factor-alpha as biomarkers of exposure to indoor pollutants among primary school children in Klang Valley - Jalaludin, Juliana; Syed Noh, Sharifah Nazariah; Suhaimi, Nur Faseeha; Md. Akim, Abdah (Science Publications, 2014)
Poor indoor air quality can be particularly harmful to children and interfere with the growth of their lung function as they spend much of their time indoors. In order to understand the mechanism of exposure in the airways, biomarkers were used as a surrogate for biological responses towards indoor air pollutants. This study aims to investigate the association between indoor air pollutants (PM2.5, PM10 and NO2) among school children in different area of urban and rural site in Klang Valley. A cross sectional comparative study was conducted among 430 healthy schoolchildren from a national primary school. Methods involved questionnaires based on American Thoracic Society and sputum samples for biomarkers assay. Indoor exposure to PM2.5 and PM10 (Dust Trak Aerosol Monitor) and NO2 (LaMotte Air Sampler) were measured in the classroom. Mean concentration of PM2.5 (50.72 µg/m3) in urban schools were significantly higher compared to rural (28.36 µg/m3) school. Similar trend found in indoor level of PM10 in urban and rural schools with 87.04 µg/m3 and 56.76 µg/m3 respectively. The mean exposure level of NO2 of urban schools (0.12 ppm) is nearly 4 times higher than the level in rural areas (0.032 ppm). A significant association was found between indoor air concentrations (PM2.5 and PM10) with TNF-alpha level. Children from rural areas are exposed to less air pollutants compared to those from urban area and this study also suggests that higher exposure to PM2.5, PM10 and NO2 are associated with increasing of TNF-alpha level.